2016
DOI: 10.1631/jzus.b1600078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil

Abstract: Abstract:To investigate the effect of glycitein, a synthetic soybean isoflavone (ISF), on the intestinal antioxidant capacity, morphology, and cytokine content in young piglets fed oxidized fish oil, 72 4-d-old male piglets were assigned to three treatments. The control group was fed a basal diet containing fresh fish oil, and the other two groups received the same diet except for the substitution with the same dosage of oxidized fish oil alone or with ISF (oxidized fish oil plus ISF). After 21 d of feeding, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
(60 reference statements)
3
12
0
Order By: Relevance
“…In addition to morphology measurements, jejunal antioxidant capacity and tight junction were also analysed to explore intestinal health of growing pigs . Under oxidative stress conditions, reactive oxygen species synthesis can trigger greater prevalence of pathogenic microorganisms as a result of compromised immune cell functions, which could subsequently lead to defects in gastrointestinal barrier function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to morphology measurements, jejunal antioxidant capacity and tight junction were also analysed to explore intestinal health of growing pigs . Under oxidative stress conditions, reactive oxygen species synthesis can trigger greater prevalence of pathogenic microorganisms as a result of compromised immune cell functions, which could subsequently lead to defects in gastrointestinal barrier function .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to morphology measurements, jejunal antioxidant capacity and tight junction were also analysed to explore intestinal health of growing pigs. 18,39,40 Under oxidative stress conditions, reactive oxygen species synthesis can trigger greater prevalence of pathogenic microorganisms as a result of compromised immune cell functions, which could subsequently lead to defects in gastrointestinal barrier function. 41,42 The present study showed that there were no differences in activity of antioxidant enzyme and protein expression of occludin, claudin1 and claudin3 among pigs consuming colistin sulfate or lysozyme diets.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…The homogenates were centrifuged (4,000 g for 5 min at 4°C) and the supernatants were used to determine the indices of oxidative stress. The oxidative indicators, SOD and MDA, in the breast muscle, liver, and jejunal mucosa were quantified using assay kits (Nanjing Jiancheng Bioengineering Institute, China) following the manufacturer’s instructions (31).…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al [19] reported that SI improved the immune function in young piglets fed oxidized fish oil. Moreover, Lv et al [42] reported that genistein (GEN boosted the anti-viral capacity of broilers chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavones, including genistein, daidzein, and glycitein, are similar in structure to 17-β-estradiol. Soy isoflavones are used as a supplement to improve growth performance, antioxidant activity, and immune function [14,15,16,17,18,19]. These reasons caused us to hypothesize that supplemental soy isoflavones may improve the performance and immune function of broilers chickens infected with IBDV.…”
Section: Introductionmentioning
confidence: 99%